Crítica, ideología y Aufklärung según Michel Foucault - Karczmarczyk, Pedro; Rodríguez Feilberg, Norma Beatriz (2011)
Analizamos la pregunta de Michel Foucault por estatuto de la crítica y su reflexividad: ¿de qué manera puede determinarse el estatuto de su propio discurso? Recorreremos dos caminos: (i) el rechazo de la noción de ideología. La cuestión es aquí: ¿cómo es posible la crítica sin la ideología y la verdad?; (ii) la recuperación foucaultiana de la actitud crítica (en los textos sobre Kant y la pregunta Was ist Aufklärung?) y la problemática de la modernidad en términos de una "ontología histórica del presente". Ambos caminos se cruzan, ya que las observaciones sobre una "política de la verdad" (lo otro de la crítica de la ideología comprometida con una verdad aséptica) se refuerzan con las de la cuestión del gobierno en términos de una "inservidumbre voluntaria". En ambos casos, la práctica de la crítica, que subjetiviza desujetando, plantea la cuestión de la libertad
We analyze Michel Foucault's question for the status of critique and its reflexive return over Foucault himself: How Foucault's discourse, qua critique, should be understood? We will drive two paths: (i) the refusal of the notion of ideology, where the question is: How to think of critique without ideology and truth?; (ii) the Foucauldian recovery of the "critical attitude" (in the texts on Kant's answer to the question Was ist Aufklärung?) and of the problem of modernity, along the lines of a "historical ontology of the present". There is a crossroad of (i) and (ii), since the remarks on a "politics of truth" (as opposite to an "ideology critique" committed with an aseptic truth) reinforces mutually with the problem of the government, faced along the lines of an art of the "voluntary inservitude". In both cases, practice of criticism that subjectifies desubjugating, poses the question of liberty
Keywords: Ideología; Verdad; Poder; Modernidad; Sujeto; Ideology; Truth; Power; Modernity; Subject